2022
DOI: 10.1371/journal.pone.0268375
|View full text |Cite
|
Sign up to set email alerts
|

A national study of moral distress among U.S. internal medicine physicians during the COVID-19 pandemic

Abstract: Background There have been no studies to date of moral distress during the COVID-19 pandemic in national samples of U.S. health workers. The purpose of this study was to determine, in a national sample of internal medicine physicians (internists) in the U.S.: 1) the intensity of moral distress; 2) the predictors of moral distress; 3) the outcomes of moral distress. Methods We conducted a national survey with an online panel of internists, representative of the membership of the American College of Physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…This is higher than for other surveys of the medical profession [22]. The sample also represents the population of practising physicians in Norway in key aspects like gender, age and workplace [23]. This provides a reasonable basis for generalisation but does not entirely rule out the possibility of nonresponse bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is higher than for other surveys of the medical profession [22]. The sample also represents the population of practising physicians in Norway in key aspects like gender, age and workplace [23]. This provides a reasonable basis for generalisation but does not entirely rule out the possibility of nonresponse bias.…”
Section: Discussionmentioning
confidence: 99%
“…To learn how these changes impact moral distress over time, longitudinal studies are needed [22]. Few longitudinal studies of moral distress exist, and the available ones are of short duration (weeks or months) [23][24][25]. The Norwegian Physician Panel makes it possible to compare the same physicians over time.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been suggested to reduce moral distress among clinicians. Managers of outpatient practices should understand what moral distress means for clinicians and its importance to them, create supportive work environments, create ways for clinicians and staff to learn and talk about moral distress and safely raise morally distressing issues, identify and address any ongoing sources of moral distress, and provide clinicians with needed psychological support and time away from work 10 12 86 90 91. Clinicians should be involved in operational decisions made during challenging times—indeed, all times—so that decisions can be informed by their perspectives and clinicians can better understand the choices available to their practices and reasoning behind the decisions made that affect them, their colleagues and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was designed as a screening tool targeted toward nurses in a hospital setting and has good convergent and discriminant validity ( Wocial and Weaver, 2013 ). It has been used to measure moral distress in HCPs ( Mehlis et al, 2018 ; Sonis et al, 2022 ). The Japanese translation of the Moral Distress Thermometer was handled by a native English-speaking researcher who is fluent in Japanese and a Japanese-speaking researcher who is fluent in English.…”
Section: Methodsmentioning
confidence: 99%
“…HCPs in oncology might be prone to moral distress when deciding between cancer care and infection control. Moral distress is defined as the discomfort felt when a person, institution, or situation prevents a HCP from doing what he or she believe is morally right in health care ( Sonis et al, 2022 ). Studies of moral distress among HCPs related to the COVID-19 pandemic have shown associations between moral distress and mental health issues, including anxiety, depression and post-traumatic stress disorder (PTSD; Norman et al, 2021 ; Petrisor et al, 2021 ; Schneider et al, 2021 ; Lake et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%